KAJIAN HUKUM PASAL 27 AYAT (3) UU ITE TERHADAP KEBEBASAN BERKESPRESI STAND UP COMEDIAN DALAM MENYAMPAIKAN JOKE - Heru Heru (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Stand-up comedy is an art form that provides a lot of criticism of social norms or phenomena that are currently occurring in society. This research aims to analyze the meaning of article 27 paragraph (3) of the ITE Law and the limits on the freedom to present jokes via electronic media from the perspective of the ITE Law. The method that will be used is a normative study method or statutory approach by analyzing Article 27 paragraph (3) of the ITE Law by referring to the text of Article 27 paragraph (3) of the ITE Law. This research found that this article has a broad definition and multiple interpretations, which has the potential to be applied inconsistently and is susceptible to misuse to silence criticism through stand-up comedy jokes. This research concludes that the existence of Article 27 paragraph (3) of the ITE Law can limit the freedom of expression of comics in presenting their comedy material.